2023
DOI: 10.1002/mds.29527
|View full text |Cite
|
Sign up to set email alerts
|

Brain MRI in Progressive Supranuclear Palsy with Richardson's Syndrome and Variant Phenotypes

Mike P. Wattjes,
Hans‐Jürgen Huppertz,
Nima Mahmoudi
et al.

Abstract: BackgroundBrain magnetic resonance imaging (MRI) is used to support the diagnosis of progressive supranuclear palsy (PSP). However, the value of visual descriptive, manual planimetric, automatic volumetric MRI markers and fully automatic categorization is unclear, particularly regarding PSP predominance types other than Richardson's syndrome (RS).ObjectivesTo compare different visual reading strategies and automatic classification of T1‐weighted MRI for detection of PSP in a typical clinical cohort including P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…This significant midbrain atrophy aligns well with the clinical manifestations commonly observed in patients with sporadic PSP-RS. In summary, the patient's MRI findings are consistent with established literature, reinforcing their diagnosis as a case of PSP-RS (53)(54)(55).…”
Section: Discussionsupporting
confidence: 84%
“…This significant midbrain atrophy aligns well with the clinical manifestations commonly observed in patients with sporadic PSP-RS. In summary, the patient's MRI findings are consistent with established literature, reinforcing their diagnosis as a case of PSP-RS (53)(54)(55).…”
Section: Discussionsupporting
confidence: 84%
“…After duplicate record elimination, 1096 records were screened by reviewing the title and abstract, eliminating 702 further studies. For the 337 remaining records, full texts were reviewed, eliminating 315 records (unrelated content: n = 280; patient or control group consisting of <10 subjects: n = 22 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]; full text unavailable: n = 1 [38]; non-extractable data: n = 1 [39]; data in median/quartiles: n = 4 [40][41][42][43]; identical study cohorts or study cohorts with significant overlap: n = 2 [8,44]; data on PSP/MSA cohorts without distinction of RS/MSA-P phenotypes: n = 5 [45][46][47][48][49]). Five studies were identified via manual search of related papers, references, and citing papers [13,[50][51][52][53].…”
Section: Literature Search and Screening Resultsmentioning
confidence: 99%